2019
DOI: 10.1109/tnb.2019.2900466
|View full text |Cite
|
Sign up to set email alerts
|

ISI-Aware Channel Code Design for Molecular Communication via Diffusion

Abstract: In molecular communication via diffusion, information molecules diffusing in the environment are subject to Brownian motion. Due to probabilistic propagation, the arrival of the molecules at the receiver is spread in time, leading to the reception of some molecules belonging to the previous symbol(s) during the upcoming symbol duration. Known as inter-symbol interference (ISI), this problem has been extensively studied in the literature by applying a large spectrum of techniques, mostly inspired by approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 25 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…The value of p that maximizes (11) is determined by differentiating (11) and equating it to zero. It is found that its value is p = 1/I.…”
Section: Lower Bound On the Number Of Received Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of p that maximizes (11) is determined by differentiating (11) and equating it to zero. It is found that its value is p = 1/I.…”
Section: Lower Bound On the Number Of Received Moleculesmentioning
confidence: 99%
“…An energy efficient coding technique for MC was introduced in [10]. An ISI-aware channel coding technique that incorporates the effect of ISI in channel code design for DBMC channel was proposed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…A binomial distribution B(n, p) can be approximated with a normal distribution N (np, np(1 − p)), when n is greater than 50 [25], [44]. Since in the considered scenario n is significantly higher than 50, as shown in Figure 8a, eq.…”
Section: B Isi Analysismentioning
confidence: 99%
“…In that scenario, the communication is based on pheromone transmission using unspecified molecules which diffuse through the blood medium, where the propagation distance is larger than the length of a single cell [20], [21]. We describe the potassium ion propagation within the cardiomyocyte cytosol with the diffusion-based MC models [22]- [25] and ground this study on the system model presented in [23]. We assume that 1) the potassium ion transmitter is a point source which integrates the ions transmitted via gap junctions from the neighboring cells and/or externally injected ions (e.g., via electrophoresis), 2) the potassium ions movement in the intracellular space can be characterized by the diffusion law, and 3) the potassium ion receiver absorbs or accumulates the ions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also showed that their coding gain can be increased by re-defining according to this distance metric, the decoding region of Hamming codes. In [24], the authors considered transition probability for each codeword to another; they also introduce several heuristics and a mixed integer programming model to produce codebooks that are minimizing the transition probabilities is introduced. In this work, it was shown that the designed codebooks achieve, for high data rates, a considerably low BER performance.…”
Section: Introductionmentioning
confidence: 99%